KUALITAS PELAYANAN KEPEMILIKAN AKTA PERKAWINAN DALAM PEMERATAAN TERTIB ADMINISTRASI KEPENDUDUKAN DI (DISDUKCAPIL) KABUPATEN BULELENG - Widiantari, Ni Kadek Linda; Supriliyani, Ni Wayan; Sastra WIjaya, Komang Adi (CITIZEN CHARTER, 2021)
The increase in the marriage rate is related to the administrative order of ownership of a marriage certificate for the people of Buleleng Regency. This study aims to determine the quality of ownership of a marriage certificate in an orderly population administration at the Population and Civil Registry Office of Buleleng Regency. The research used a qualitative approach with descriptive research. Collecting data in this study using the method of observation, interviews and documentation. The results show that the service quality of marriage certificates in orderly population administration has shown a good increase, seen from the satisfaction of the community in providing services, but there are still obstacles in the process of service delivery for marriage certificates that are carried out offline / online. in the Disdukcapil Office namely on the reliability aspect, the responsivisness aspect, the assurance aspect, then the empathy aspect, finally the tangibles aspect. Keywords: Service Quality, Marriage Certificate, Population Administration